Opportunities and Challenges Driven by the Wave of Technology: A Comparative Empirical Study of Digital Library Management Models in Chinaand the United States - Nan Liu (Journal of Frontier in Economic and Management Research, 2025)
Under the background of the era when the technological wave drives globalization and informatization, this paper reveals the characteristics and differences of the development of digital libraries in China and the United States by comparing and analyzing the management models of digital libraries in the two countries. The research finds that China’s digital libraries take the top-level design led by the government as the core and promote resource integration and equalization of services through national-level projects. The United States, relying on a multi-party collaboration model, emphasizes the two-way drive of technological innovation and user demands. There are significant differences between the two countries in terms of strategic layout, technology application, service innovation, etc., but they also show a trend of mutual learning: China needs to enhance the level of technological autonomy and service refinement, and the United States can refer to China’s experience in systematic strategic promotion. This study provides an empirical reference for the optimal development of digital libraries worldwide.